GOODS AND APLIKASI PENCATATAN STOCK PENJUALAN UNTUK TOKO GROSIR DENGAN MENGGUNAKAN MICROSOFT VISUAL BASIC 6.0 - Yogo Bhakti Prabowo; Erick Orlando, SKom, MMSI (Jurnal Sistem Informasi, 2005)
In scientific writing, the writer explains the design stock listing application for the sale of goods and grocery stores with using Microsoft Visual Basic 6.0. in this application program consist of 11 form. And use the program to connect to a database object data access. As well as using Microsoft Access 2003 for database.